DNA isolation for PCR amplification and molecular identification of marine sponges collected in Con Dao Islands, Vietnam - Nguyen, Quang Hung; Nguyen, Chi Mai; Pham, Thi Hoe; Hoang, Dinh Chieu; Luu, Hoa Xuan; Nguyen, Van Tuong; Le, Quang Trung; Vu, Huong Giang; Ninh, Khac Ban; Le, Quynh Lien; Tran, My Linh (Academia Journal of Biology, 2025)
Molecular approaches based on DNA sequences have become increasingly indispensable in modern taxonomy, particularly for taxa with few or ambiguous diagnostic morphological characters, such as sponges. However, genomic DNA isolation from sponges is often hindered by abundant secondary metabolites. Here, we optimized a CTAB-based DNA extraction protocol by adjusting the concentrations of CTAB, SDS, and proteinase K. The optimized extraction buffer (4% CTAB, 1% SDS, and 5 µg/mL proteinase K) substantially improved DNA yield and purity. Applied to six sponge specimens from the Con Dao Islands, the protocol yielded DNA concentrations exceeding 200 ng/µL from 100–300 mg of tissue, with purity ratios indicative of high-quality DNA. DNA integrity was confirmed by successful PCR amplification of the mitochondrial cytochrome c oxidase subunit I (COI) gene fragment. Sequence analyses corroborated morphological identifications and enabled species-level assignment of four specimens. Together, these results demonstrate that the optimized extraction protocol provides a reliable and effective approach for obtaining high-quality genomic DNA from sponges, thereby facilitating molecular identification and supporting taxonomic and phylogenetic studies of marine sponges.